Level of Support for Disability as Diversity in Special Education Institutions - Iram Batool Alvi, Faisal Anis (JIE, 2024)
Teaching students with special needs require certain type of support during education. Majority of the special education institution in Pakistan cater more than one disability which requires multifaceted type of support to manage the diverse educational needs. This paper describes the level of support in special education institutions for children with disabilities. The research design is quantitative by nature.